Over‐expression of ATR causes autophagic cell death. (25th January 2013) - Mori, Chihiro; Yamaguchi, Yoshihiro; Teranishi, Mika; Takanami, Takako; Nagase, Takahiro; Kanno, Shinichiro; Yasui, Akira; Higashitani, Atsushi
<x xml:space="preserve">Abstract</x> ATR is highly conserved in all eukaryotes and functions as a cell‐cycle checkpoint kinase to stabilize the nuclear genome. In addition, knockout mouse models indicate that ATR is essential for viability. Here, it is shown that moderate overproduction of ATR, but not of the other phosphatidylinositol 3′ kinase‐related kinases, ataxia‐telangiectasia‐mutated, mTOR and SMG‐1, and a downstream target p53, resulted in cell death. ATR over‐expression induced cellular vacuolization from 12 to 48 h after transfection, before cell death progression. A series of deletion analyses showed that overproduction of the N‐terminal HEAT repeat segments of ATR was sufficient for the induction of the vacuolization. Moreover, post‐transcriptional modification of LC3, a marker of autophagy, and autophagosomes with double membranes were evident in ATR‐overproducing cells. The vacuolization was also suppressed in autophagy‐deficient MCF7 cells. In addition, both cellular vacuolization and cell death were reduced by inhibition of Ras activity using farnesyl thiosalicylic acid. Conversely, neither inhibition of mTOR nor activation of the checkpoint system could be observed in the vacuolated cells. These results suggest that the Ras signaling pathway is involved in the autophagic response caused by ATR overproduction, and tight regulation of ATR protein expression is crucial for cell viability.